Therapeutic Effect of His-Purkinje System Pacing Proportion on Persistent Atrial Fibrillation Patients With Heart Failure - Tong, Fei; Sun, Zhijun (Frontiers in Cardiovascular Medicine, 2022)
His-Purkinje system pacing(HPSP) combined with atrioventricular node (AVN) ablation is an effective therapy for atrial fibrillation (AF) patients with heart failure (HF).However, AVN ablation is accompanied with some limitations and disadvantages. HPSP combined with β -blocker reduces inherent heart rate and increases pacing ratio, which may be an alternative to HPSP combined with AVN ablation. This study was to assess the therapeutic effect of different His-Purkinje system pacing proportions on AF patients with HF. Methods The study enrolled 30 consecutive persistent AF patients with HF who underwent HPSP. Heart rate was controlled by medical therapy. New York Heart Association (NYHA) classification, serum NT-proBNP concentration, echocardiographic parameters were assessed at each follow-up. Results The AUC of pacing proportion for predicting MACE was 0.830 (SE=0.140, 95%CI:0.649-0.941, P=0.018), the best cut-off value of pacing proportion to predict MACE by ROC analysis was 71% (sensitivity:83.3%, specificity: 91.7%). In high pacing proportion group(>71%), there were significant improvements of NYHA classification, NT-proBNP concentration, LVEF and LVEDD from the baseline in wide QRS complex (QRSd>120ms) patients and HFrEF patients at half year follow-up, and there were significant improvements in NYHA classification, NT-proBNP concentration from baseline in narrow QRS complex (QRSd≤120ms) patients and HFpEF patients at half year follow-up, moderate but no significant improvements of LVEF and LVEDD were observed in those patients groups. In low pacing proportion group(≤71%), there were no significant improvements of NT-proBNP concentration, LVEDD or LVEF regardless of baseline QRS duration or LVEF (P > 0.05). Conclusion High pacing proportion(>71%) of HPSP can improve clinical outcomes and echocardiographic parameters in persistent AF patients with wide QRS complex or HFrEF, and clinical outcomes in persistent AF patients with narrow QRS complex or HFpEF. High pacing proportion of HPSP has a beneficial effect on the prognosis of persistent AF patients with heart failure.